THE INFLUENCE OF SELLING PRICES AND EXCHANGE RATES ON BARECORE EXPORT VOLUME - Reisi Rizqie Auliya; Dody Setyadi; Nur Rini (Politeknik Negeri Semarang, 2018)
The aim of this study is to examine the influence of selling prices and exchange rates on export volume of barecore both simultneously and partially. The study utilized quantitive research method. Secondary data used were monthly period data from January 2012 – December 2017. The data sources were from export department of PT. Albasia Sejahtera Mandiri Head Office in Kabupaten Semarang and Bank Indonesia. The total data used were seventy two. The study explored with multiple linear regression statistic analysis. The t-Test result informed that the selling prices and exchange rates partially influenced significantly the export volume of barecore. The F-Test informed that selling prices and exchange rates influenced simulataneously on barecore’s export volume significantly. Regarding the results, in order to increase the export volume of barecore, PT. Albasia Sejahtera Mandiri needs to set more competitive selling prices they offer to importers. In addition, other things that must be considered by PT Albasia Sejahtera Mandiri is that export volumes are sensitive to exchange rate fluctuations. Another strategy to improve export performance is with market expansion and development of product variants offered to importers.